Formação e trabalho das equipes gestoras de educação infantil - Reis, Marcela Lemos Leal (2015)
In the complexity of Teachers` formation and playing field regarding Children's Education, the research is held within the scope of educational service discussion of 0 to 5 year-old children as a more direct responsibility of the municipal public management, addressing the formation of the professionals working at the Municipal Secretary of Education. The purpose of the work is to understand how the Children's Education managers teams are configured and their work dynamic interface with the challenge of professional formation and acting. On the basis of understanding a subject as active (BAKHTIN, 2011), observing the formation as a lifelong formative process, composing a know-how itself and enhancing personal and professional dimensions before the teaching work complexity (NÓVOA, 2002, 2007). In this context, the professional formation, educational institutions and the actions demanded by function in interaction with work possibilities are considered essential to the discussion of the consistency of such Children's Education managers teams actuation and their formation processes. It elects the methodological choice through the qualitative and exploratory approach research, with the procedure to apply a questionnaire, supported in the initial stage of work observation of the Children's Education managers teams in the Espírito Santo State context. In the set of all challenges posed to service quality regarding Children's Education, the data related to the professionals profile, performance dynamic in the context of work and formative experiences of the Children's Education team managers highlight the importance to guarantee discussions that bring the specificities of the elementary education first stage and the issues relevant to Children's Education management, in the initial and continuing formation and indicate the commitment with a quality education.